Pragmatic Function Shifts in the Translation of WH Questions in “500 Days of Summer” - Prahara, Muhammad Afrizal Lutfi (Jurnal Bahasa, Sastra, dan Studi Amerika, 2021)
The author is analyzing and conducting a translation research in interrogative utterances from the film "500 Days of Summer" especially WH questions, because WH questions not only contain information at the surface structure, but also pragmatic functions within them. This study is being carried out in order to help the writer and readers understand interrogative sentences more clearly. This research is conducted under Translational research using a descriptive qualitative method. The analysis applies the theory of Nida & Taber’s translation theory, Newmark’s translation theory, Mona Baker’s translation techniques theory, Marcella Frank’s interrogative sentences theory and Nababan, Nuraeni & Sumardiono’s translation quality assessment theory. The scope of this research is a translational analysis of a film subtitle. This research focuses on the translation of interrogative utterances in the form of WH questions in the film "500 Days of Summer" specifically character dialogues. This research intends to investigate the pragmatic function of the utterances on the target language, as well as the pragmatic differences that may exist between the source and target languages, as well as the translator's translation techniques, including their impact on translation quality.